Social Media “X” on Enhancing EFL Students’ Writing Skills: A Study of Positive and Negative Impacts - Sabillah, Ifadatus; Sa’diyah, Abdiyatus; ., Irmayani (STAI Bani Saleh, 2025)
This study examines the impact of the social media platform “X” on enhancing students’ English writing skills, focusing on both positive and negative effects. Employing a mixed-methods approach involving qualitative interviews, surveys, and quantitative analysis, the research delves into how social media “X” influences students’ ability to write proficiently in English. Findings from the study reveal a significant positive impact on students’ English communication skills and vocabulary expansion through global discussions on “X.” However, negative impacts include a lack of attention to proper language structure, reliance on abbreviations leading to reduced depth of expression, and potential hindrance in using English correctly. Insights from this research contribute to understanding the nuanced dynamics of social media’s role in language learning and inform pedagogical strategies for optimizing digital platforms in education.